Improvement of Farmers Economy through Frontline Demonstrations conducted at VUTRC, Trichy - V. Jayalalitha; K. Shibi Thomas; P .N. Richard Jagatheesan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Proven scientific technologies related to the Animal Husbandry practices are generally demonstrated in the field for the benefit of the farmers. Veterinary University Training and Research Centre, Tiruchirappalli has conducted three frontline demonstration programmes (FLD) during the year 2015 - 2018. By these programmes, it is observed that farmers get benefitted economically. Twenty farmers were benefitted in the programme conducted in 2015-16 on the "Impact of TANUVAS mineral mixture on the milk yield of dairy cows". Mineral mixture supplementation improved the milk quality and milk quantity. Hence each farmer obtained additional improved returns of Rs.150/month/cow. In the year 2016-17 a programme on "Scientific intervention in to Improve Production Performance of Backyard native chicken" was conducted and four farmers were benefitted. They reported that the scientific technologies like TANUVAS desi chicken feed, deworming and vaccination demonstrated in this programme increased body weight gain, reduced mortality, increased egg production and improved hatchability. Each farmer profited Rs.500/- for 5 birds additionally. Six farmers participated and benefitted in the programmes conducted in 201718 on "Azolla pinnata as cattle feed supplement". Supplementation of azolla reduces the cost of production of milk and improves the milk quality. In this study it is observed that there was a reduction in cost of production of about Rs.2.50 / litre of milk Also there was an increase in returns of milk since improved quality of milk